Recruitment, Job Placement and Employee Performance - Syafaruddin, Syafaruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to investigate and analyze the impact of recruitment and job placement on employee performance at PT. Semen Tonasa, specifically within the Distributor Division, is in Makassar City. The research explores how these human resource management practices influence work outcomes and whether their effective implementation can enhance employee performance. Research Design and Methodology: The study's population consists of 40 employees from the distribution section of PT. Semen Tonasa in Makassar City. A census sampling method was utilized, involving all population members as the sample. Primary data was gathered through direct questionnaires distributed to the respondents. The analysis methods included descriptive statistics, validity and reliability testing, normality testing, multicollinearity testing, hypothesis testing using multiple linear regression analysis, partial and simultaneous tests, and determination coefficient tests. Findings and Discussion: The findings demonstrate that recruitment and job placement positively and significantly affect employee performance at PT. Semen Tonasa's Distributor Division, both individually and collectively. These results indicate that implementing effective recruitment and placement strategies can significantly improve employee performance, aligning with theoretical expectations regarding human resource practices' role in organizational success. Implications: The study's results underscore the critical importance of strategic recruitment and job placement in enhancing employee performance. These findings suggest organizations should refine these HR practices to foster better employee outcomes. Further research is recommended to explore these relationships in different organizational contexts and industries to expand the applicability of these results.